2016
DOI: 10.3762/bjoc.12.56
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of α-pyrones

Abstract: SummaryThe α-pyrone moiety is a structural feature found in a huge variety of biologically active metabolites. In recent times new insights into additional biosynthetic mechanisms, yielding in such six-membered unsaturated ester ring residues have been obtained. The purpose of this mini-review is to give a brief overview of α-pyrones and the mechanisms forming the basis of their natural synthesis. Especially the chain interconnecting enzymes, showing homology to ketosynthases which catalyze Claisen-like conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 90 publications
2
66
0
Order By: Relevance
“…The inhibition of this compound may be due to pyrimidin and pyran rings. [12][13][14][15][16][17][18][19] Our results agree with Najafian 11) he reported that curcumin inhibited α-amylase with an half maximal inhibitory concentration IC 50 value 51.32 µM. Curcumin at different concentrations, i.e., 10, 50, 100 µg showed dose dependent effect where as the standard indomethacin at 50 and 100 µg exhibited much higher activity.…”
Section: α-Amylase Inhibitory Activity By Curcumin Derivativessupporting
confidence: 85%
See 2 more Smart Citations
“…The inhibition of this compound may be due to pyrimidin and pyran rings. [12][13][14][15][16][17][18][19] Our results agree with Najafian 11) he reported that curcumin inhibited α-amylase with an half maximal inhibitory concentration IC 50 value 51.32 µM. Curcumin at different concentrations, i.e., 10, 50, 100 µg showed dose dependent effect where as the standard indomethacin at 50 and 100 µg exhibited much higher activity.…”
Section: α-Amylase Inhibitory Activity By Curcumin Derivativessupporting
confidence: 85%
“…Compounds 5, 6 and 7 exhibited significant inhibitory activity against histamine and was comparable with that of original curcumin. Compound 5 showed 29.35±2.5, 36.82±2.1, [12][13][14][15][16][17][18][19] Curcumin has been reported to have anti-allergic effects and can inhibit the release of histamine from mast cells. 27) The histamine release from compound 48/80-treated RPMCs was reduced in a dose-dependent manner by curcumin (58 and 80% inhibition at 25 and 50 µM, respectively).…”
Section: α-Amylase Inhibitory Activity By Curcumin Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…a-Pyrone, a six-membered lactone, is frequently discovered in microorganisms, plants, and animals, and is oen substituted with a side chain. 16 The diverse substitutions of the six-membered lactone, as well as the variations in length and substitutions of the side chain, greatly contribute to the structural diversity and complexity of a-pyrone derivatives. [17][18][19][20][21] Compounds 1-4 are new a-pyrone derivatives containing an unusual dimethyl substitution in the highly unsaturated side chain (Fig.…”
Section: Hz)mentioning
confidence: 99%
“…Their plausible biosynthetic pathway was proposed through a polyketide synthase. 16 A linear polyketide chain was rst constructed from an acetyl coenzyme A (CoA) and six malonyl-CoA followed by reduction, dehydration, methylation, oxidation, or cyclization to generate the a-pyrone derivatives.…”
Section: Hz)mentioning
confidence: 99%